Barnardo's Scotland welcomes Ukraine service - Kirsty-Louise Hunt; Karen Campbell; David Findlay (Scottish Journal of Residential Child Care)
Barnardo’s has a long history of helping people seeking sanctuary in the UK, and today our work includes supporting children and families that have arrived after fleeing the invasion of Ukraine more than a year ago. The Barnardo’s support to families from Ukraine over the past year builds on our significant experience across the UK of supporting refugees arriving from Afghanistan and Syria through a range of services. As the largest children’s charity in the UK – with more than 150 years of experience supporting children and families – Barnardo’s is able to provide the co-ordination and structure through which those displaced from Ukraine can be welcomed into a safe environment with support in place to ensure their needs are met. We fully understand that families fleeing Ukraine are likely to have experienced significant trauma and have limited resources, which, when combined, makes them highly vulnerable. In Scotland, we have developed the ‘Barnardo’s Scotland Welcome (Ukraine) Service’ because we recognised the need to reach those children, young people and families coming to Scotland to seek refuge from the war against Ukraine. This article sets out the details of the Barnardo’s Scotland response to the crisis and our learnings so far, in Scotland and across the UK, from the support we’ve provided.